Application of IMU Sensors for Analyzing Human Lower Limb Motion Dynamics - Jelenska, Julia (2025 26th International Carpathian Control Conference (ICCC), 2025)
This study investigates human lower limb dynamics using IMU (Inertial Measurement Unit) sensors-accelerometers, gyroscopes, and magnetometers-within a motion capture system. By analyzing kinematic and dynamic parameters during walking and running, we identify critical gait phases and characterize lower limb motion as a system of coupled oscillators. Our findings reveal dominant muscle and joint frequencies that define the primary locomotor rhythm. Additionally, we highlight the synchronized interplay between upper and lower limbs, emphasizing the role of arm movements in balance and stability. Through velocity and acceleration analyses across multiple planes, this research provides a comprehensive spectral and phase-based perspective on gait dynamics. These insights enhance biomechanical models for medical diagnostics and sports performance while informing bipedal robotic control algorithms. Findings underscore the systemic nature of human motion and open new avenues for studying adaptive gait strategies and robotic gait emulation. This research was conducted at the AGH University of Krakow, as part of the Excellence Initiative-Research University program.